Penataran Ilmu Agama di Kelurahan Kalebajeng Kecamatan Bajeng Kabupaten Gowa - Iskandar Iskandar; Rahmat Rahmat (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2022)
Real Work Lecture (KKN) STIBA Makassar Batch V in Kalebajeng Village, Bajeng Subdistrict, Gowa Regency, aims to do community service as a form of the Tridarma Perguruan Tinggi. The method of implementing the service program begins with mapping the problems and needs of the community using SOAR Analysis. After the analysis is carried out, the work program is prepared according to the needs of the community. Work programs that have been successfully implemented are Body Management Training, Fiqh Studies of Worship, Tahsinul Qira'ah and Ramadan Islamic Boarding Schools. All of these work programs have been implemented and have shown good initial results and will be followed up by the Wahdah Islamiyah Branch Leadership Council, Bajeng District, Gowa Regency.